Sustainable use of ecosystem services under multiple risks: a survey of commercial cattle farmers in semi-arid rangelands in Namibia - Roland Olbrich; Martin F. Quaas; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
Studying the sustainable use of ecosystem services under uncertainty requires the consideration of the stochastic dynamics of the system under study, risk and time preferences, risk management strategies and normative views pertaining to sustainability. To gather this information for an important ecological-economic system, we conducted a survey of commercial cattle farmers in semi-arid rangelands of Namibia, a system that features risks on various space and time scales. Here we present a description of the research aims, design and conduction of the survey, and analyze and discuss the homogeneity and representativeness of our survey population. The survey consisted of a mail-in questionnaire and in-field experiments. We combined two existing farm-address databases, reaching 77% of the estimated 2,500 cattle farmers. The return rate of questionnaires exceeded 20%, and response rate to individual questions surpassed 95% and 90% for the majority of non-sensitive and sensitive questions, respectively. Distinct sub-sample groups within the survey population did not differ in the analyzed characteristics with the exception of ethnicity, regional location of farmland and an intentionally induced bias for residency on farm. It has turned out that we have undersampled distinct population segments of farmers, such as indigenous farmers or farmers not belonging to the main interest group of commercial cattle farming. Notwithstanding, we consider the survey to be highly successful, yielding a rich dataset which allows diverse analyses.
Keywords: Q12; Q15; Q24; Q56; Q57; 330; Survey; cattle farming; semi-arid; rangeland management; sustainability; risk